2018
DOI: 10.1111/nmo.13335
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and mechanical properties of the anal sphincter muscles in healthy senior volunteers

Abstract: This work reports baseline parameters describing the morpho-mechanical condition of the sphincter muscle of healthy elderly volunteers. New parameters were also proposed to quantify the active properties of the muscles based on the mechanical energy associated with muscle contraction and fatigue. This information could be used to assess patients suffering from AI or for the design of novel implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…While the methodology used was quite similar among all studies, there is until now, no consensus about the best parameters to record with FLIP technology. Several parameters have been suggested from the most complexes (anal canal stiffness defined on the basis of the pressure and diameter changes when the volume increased from 1 to 50 mL, 93‐95 flow resistance of the anal canal defined from the anal canal length, the middle part diameter of the anal canal and the dynamic viscosity of the inflated bag 96 or mechanical work of the anal sphincter muscle, 97 to the most simple (wall tension (T = P.r), 98 anal DI (CSA/P), 99,100 anal compliance (D/P), 97 yield pressure when the most resistant (middle) part of the sphincter begins to distend 93‐95 . More recently, Zifan et al described the use of area‐pressure and area‐tension‐loop analysis of the anal sphincters and puborectalis muscles in normal subjects and fecal incontinent patients, assessing the relationship between changes in muscle length (secondary to anal distension) and muscle function 101,102 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the methodology used was quite similar among all studies, there is until now, no consensus about the best parameters to record with FLIP technology. Several parameters have been suggested from the most complexes (anal canal stiffness defined on the basis of the pressure and diameter changes when the volume increased from 1 to 50 mL, 93‐95 flow resistance of the anal canal defined from the anal canal length, the middle part diameter of the anal canal and the dynamic viscosity of the inflated bag 96 or mechanical work of the anal sphincter muscle, 97 to the most simple (wall tension (T = P.r), 98 anal DI (CSA/P), 99,100 anal compliance (D/P), 97 yield pressure when the most resistant (middle) part of the sphincter begins to distend 93‐95 . More recently, Zifan et al described the use of area‐pressure and area‐tension‐loop analysis of the anal sphincters and puborectalis muscles in normal subjects and fecal incontinent patients, assessing the relationship between changes in muscle length (secondary to anal distension) and muscle function 101,102 .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Zifan et al described the use of area‐pressure and area‐tension‐loop analysis of the anal sphincters and puborectalis muscles in normal subjects and fecal incontinent patients, assessing the relationship between changes in muscle length (secondary to anal distension) and muscle function 101,102 . Thus, although 10 studies have reported results of FLIP measurements in the anal canal in HV, 93,95,97‐99,101,103‐105 no reliable normal values are yet available because of the absence of standardized protocols for assessing and analyzing FLIP measurements. However, some of these studies have demonstrated that the geometry of the lumen and the biomechanical properties of the anal canal are not uniform during distension.…”
Section: Resultsmentioning
confidence: 99%
“…They confirmed the least compliant portion of the anal canal was at the proximal end of the EAS, where it overlaps the IAS and puborectalis, highlighting this area's role in the maintenance of continence 35 . This area also demonstrated the maximal orifice closing function during voluntary squeeze, with the thickness of the EAS correlating with the change in orifice radius during contraction 54 …”
Section: Functional Lumen Imaging Probementioning
confidence: 81%
“…Few reports to date, however, have assessed the functional cooperation between the IAS and EAS, as the two sphincters were usually examined separately. Another reason of few interests in the distal IAS-EAS complex was found in a fact that, with an aid of the levator ani muscle, a closing pressure is highest in the proximal anal canal, not in the distal [5,10,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, another term "longitudinal anal muscle" has been used in the pelvic floor anatomy [16,21,28,30]. Despite recent advances in imaging technology [5,10,22,33], few studies have evaluated site-dependent differences in the topographical relationship between the internal and external anal sphincters (IAS, EAS). Endoanal ultrasound evaluation of 12 men and 14 women showed that: (1) the anterior IAS is shorter than the posterior and lateral IAS; and (2) the distance from the lateral EAS to the pubis is significantly longer than the distance from the posterior EAS to the pubis [29].…”
Section: Introductionmentioning
confidence: 99%